Polarization of Pc3/Pc4 Geomagnetic Pulsations in the Southern and Northern Hemispheres: Experimental Data and Numerical Simulation - Zalizovski, A. V.; Sinitsin, V. G.; Yampolski, Yu. M. (Видавничий дім «Академперіодика», 2013)
Polarization of Pc3/Pc4 Geomagnetic Pulsations in the Southern and Northern Hemispheres: Experimental Data and Numerical Simulation